Measurement of the [Formula: see text] production cross-section using [Formula: see text] events with [Formula: see text]-tagged jets in [Formula: see text] collisions at [Formula: see text] and 8 TeV with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; Abreu, R; et al. (The European physical journal. C, Particles and fields, 2014)
The inclusive top quark pair ([Formula: see text]) production cross-section [Formula: see text] has been measured in proton-proton collisions at [Formula: see text] and [Formula: see text] with the ATLAS experiment at the LHC, using [Formula: see text] events with an opposite-charge [Formula: see text] pair in the final state. The measurement was performed with the 2011 7 TeV dataset corresponding to an integrated luminosity of 4.6 [Formula: see text] and the 2012 8 TeV dataset of 20.3 [Formula: see text]. The numbers of events with exactly one and exactly two [Formula: see text]-tagged jets were counted and used to simultaneously determine [Formula: see text] and the efficiency to reconstruct and [Formula: see text]-tag a jet from a top quark decay, thereby minimising the associated systematic uncertainties. The cross-section was measured to be: [Formula: see text]where the four uncertainties arise from data statistics, experimental and theoretical systematic effects, knowledge of the integrated luminosity and of the LHC beam energy. The results are consistent with recent theoretical QCD calculations at next-to-next-to-leading order. Fiducial measurements corresponding to the experimental acceptance of the leptons are also reported, together with the ratio of cross-sections measured at the two centre-of-mass energies. The inclusive cross-section results were used to determine the top quark pole mass via the dependence of the theoretically predicted cross-section on [Formula: see text] giving a result of [Formula: see text][Formula: see text] GeV. By looking for an excess of [Formula: see text] production with respect to the QCD prediction, the results were also used to place limits on the pair-production of supersymmetric top squarks [Formula: see text] with masses close to the top quark mass, decaying via [Formula: see text] to predominantly right-handed top quarks and a light neutralino [Formula: see text], the lightest supersymmetric particle. Top squarks with masses between the top quark mass and 177 GeV are excluded at the 95 % confidence level.